A focused review of synthetic applications of Lawesson’s reagent in organic synthesis - Khatoon, Hena; Abdulmalek, Emilia (Multidisciplinary Digital Publishing Institute, 2021)
Lawesson’s reagent (LR) is a well-known classic example of a compound with unique construction and unusual chemical behavior, with a wide range of applications in synthetic organic chemistry. Its main functions were rounded for the thionation of various carbonyl groups in the early days, with exemplary results. However, the role of Lawesson’s reagent in synthesis has changed drastically, and now its use can help the chemistry community to understand innovative ideas. These include constructing biologically valuable heterocycles, coupling reactions, and the thionation of natural compounds. The ease of availability and the convenient usage of LR as a thionating agent made us compile a review on the new diverse applications on some common functional groups, such as ketones, esters, amides, alcohols, and carboxylic acids, with biological applications. Since the applications of LR are now diverse, we have also included some new classes of heterocycles such as thiazepines, phosphine sulfides, thiophenes, and organothiophosphorus compounds. Thionation of some biologically essential steroids and terpenoids has also been compiled. This review discusses the recent insights into and synthetic applications of this famous reagent from 2009 to January 2021.